P-Aminobenzoic acid protonation dynamics in an evaporating droplet by ab initio molecular dynamics. Issue 35 (27th August 2021) - Batista, Patrick R.; Penna, Tatiana C.; Ducati, Lucas C.; Correra, Thiago C.
Abstract : Solvent stabilization controls the protonation equilibria in evaporating droplets. Abstract : Protonation equilibria are known to vary from the bulk to microdroplet conditions, which could induce many chemical and physical phenomena. Protonated p -aminobenzoic acid (PABA + H + ) can be considered a model for probing the protonation dynamics in an evaporating droplet, as its protonation equilibrium is highly dependent on the formation conditions from solution via atmospheric pressure ionization sources. Experiments using diverse experimental techniques have shown that protic solvents allow formation of the O-protomer (PABA protonated in the carboxylic acid group) stable in the gas phase, while aprotic solvents yield the N-protomer (protonated in the amino group) that is the most stable protomer in solution. In this work, we explore the protonation equilibrium of PABA solvated by different numbers of water molecules ( n = 0 to 32) using ab initio molecular dynamics. For n = 8–32, the protonation is either at the NH2 group or in the solvent network. The solvent network interacts with the carboxylic acid group, but there is no complete proton transfer to form the O-protomer. For smaller clusters, however, solvent-mediated proton transfers to the carboxylic acid were observed, both via the Grotthuss mechanism and the vehicle or shuttle mechanism (for n = 1 and 2). Thermodynamic considerations allowed a description of the origins of the kinetic trapping effect, which explains the observation of the solution structure in the gas phase. This effect likely occurs in the final evaporation steps, which are outside the droplet size range covered by previous classical molecular dynamics simulations of charged droplets. These results may be considered relevant in determining the nature of the species observed in the ubiquitous ESI based mass spectrometry analysis, and in general for droplet chemistry, explaining how protonation equilibria are drastically changed from bulk to microdroplet conditions.